Ontogenetic Allometry of Body Height and Body Mass of Girl in Baduy, Indonesia - Eneng Nunuz Rohmatullayaly; Alex Hartana; Yuzuru Hamada; Bambang Suryobroto (Bogor Agricultural University, Indonesia, 2018)
Several small-scale populations exhibited phenotypic plasticity whereby growth spurt of body height occurred much earlier than age at menarche and this was not followed by same early spurt of body weight. This leads to question whether growth trajectory of stature follow the same growth trajectory of body mass and whether the trajectory itself is associated to sexual maturity. We evaluated developmental plasticity observed in Baduy girl, a traditional population in Indonesia, in facing strenuous environmental and biocultural conditions. We measured stature and body mass cross-sectionally. We determined age at menarche as population average of age of girls that had already got their first menstruation. Growths of body fat and weight followed a same mode and timing and their spurts pivoted on the age at menarche. In contrast, growth spurt of body height occurred four years earlier than menarche and velocity curve of body linearity progressed in opposite direction to that of body ponderality. The prevailing poor nutrition and high physical activity elicited principle of ontogenetic allometry to synchronize the acceleration and deceleration of growths in body linearity and ponderality whereby growth in body height functions to reach the body size target and to provide skeletal framework for development of body mass. The biocultural conditions lead to slow bodily growth rate with low spurt resulting in the characteristics of Baduy girl that was small in size and late in both sexual maturity and full-grown ages.